Forgiveness and gratitude as mediators between religious commitment and well-Being among Latter-day Saint Polynesian Americans - Kane, Davis K. (Mental health, religion & culture, 2021)
An abundance of research has investigated well-being as it relates to religiosity and character strengths, such as forgiveness and gratitude. However, few studies have investigated how increases in forgiveness and gratitude might explain why religious commitment enhances well-being, particularly for U.S. ethnic/racial minority populations. This study investigated if the character strengths of forgiveness and gratitude mediated the relationship between religious commitment and well-being among Latter-day Saint Polynesian Americans – a fast growing, yet understudied, population. Results indicated that forgiveness and gratitude fully mediated the relationship between religious commitment and self-esteem, and gratitude partially mediated the relationship between religious commitment and satisfaction with life. Implications for research and practice are discussed.